Read it, don't eat it! - Schoenherr, Ian. (New York : Greenwillow Books, 2009)
Rhyming text and illustrations of animals reading offer advice on how to take care of a library book.
Wilson's Children, October 2010.
School Library Journal starred, April 2009.
Book Links (A.L.A.), March 2010.
Publisher's Weekly, April 2009.
Booklist, April 2009.
Horn Book, October 2009.
Keywords: Books and reading -- Juvenile fiction; Books and reading -- Fiction; Stories in rhyme; Books and reading -- Fiction; Amimals -- Fiction